The Formation of the First Libraries in Uzbekistan and the Role of Increasing the Cultural and Educational Awareness of the Population - Muminmirzo Kholmuminov; Asilbek Qolqanatov (International Journal on Integrated Education, 2021)
The history and processes of the establishment of the first libraries in Uzbekistan have not yet been fully studied. Preliminary views were expressed on the mission of libraries in raising the ideological and political awareness of the population and the tasks of libraries. This article provides scientific research and analysis on the development of libraries as a cultural and educational organization and the history of library science. Opinions were expressed and historical materials were provided on the activities of the staff of the first libraries and the role of libraries in the political and ideological processes.